Water Harvesting for Al-Mana’i Valley in Al-Anbar Governorate Using the Surface Runoff Approach (SCS-CN) (Journal of the College of Basic Education, 2026)
For effective water resource management, a precise understanding of the hydrological behavior of the study area is crucial. The per capita share of agricultural land has witnessed a continuous decline over the years, which necessitates the development, utilization, and integrated management of related water and land resources.Surface runoff is considered a critical and essential factor in planning water management strategies. In this study, the Al-Manghi Valley Basin in Al-Anbar Governorate was selected as a case study to estimate surface runoff using the Curve Number (SCS-CN) method and Geographic Information System (GIS) techniques. Surface runoff depends on several factors, most notably rainfall intensity, soil type, soil moisture, drainage density, terrain characteristics, as well as the size and shape of the watershed and land cover. Within the GIS environment, various thematic layers were created, including soil and land use. The Curve Number (CN) was estimated polygon-wise based on a combination of land use, soil type, and Antecedent Moisture Condition (AMC). The original soil map was converted into a map representing Hydrologic Soil Groups (HSGs).GIS and Remote Sensing (RS) technologies were utilized to accurately identify areas with high surface runoff potential, enabling the selection of optimal sites for water harvesting in the study area